Health at a glance: Europe 2014 - Organisation for Economic Co-operation and Development (Paris : OECD, 2014)
This third edition presents a set of key indicators related to health status, determinants of health, health care resources and activities, quality of care, access to care, and health expenditure and financing in 35 European countries, including the 28 European Union member states, four candidate countries and three EFTA countries. The selection of indicators is based largely on the European Core Health Indicators (ECHI) shortlist, a set of indicators that has been developed to guide the reporting of health statistics in the European Union. This is complemented by additional indicators on quality of care, access to care and health expenditure, building on the OECD expertise in these areas. Compared with the previous edition, this third edition includes a greater number of ECHI indicators, reflecting progress in the availability of comparable data in the areas of non-medical determinants of health and access to care. It also includes a new chapter dedicated to access to care, including selected indicators on financial access, geographic access and timely access.
Bibliogr. odkazy
Resumé
Keywords: stav zdravotný; poskytovanie zdravotnej starostlivosti; dostupnosť zdravotníckych služieb; rozdiely v zdravotnom stave; ukazovatele zdravotného stavu; prehľady zdravotnícke; prehľady zdravotnej starostlivosti; Európa -- epidemiológia; správa výročná